2022
DOI: 10.3389/fncom.2022.854218
|View full text |Cite
|
Sign up to set email alerts
|

The Face Inversion Effect in Deep Convolutional Neural Networks

Abstract: The face inversion effect (FIE) is a behavioral marker of face-specific processing that the recognition of inverted faces is disproportionately disrupted than that of inverted non-face objects. One hypothesis is that while upright faces are represented by face-specific mechanism, inverted faces are processed as objects. However, evidence from neuroimaging studies is inconclusive, possibly because the face system, such as the fusiform face area, is interacted with the object system, and therefore the observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 38 publications
(56 reference statements)
2
12
0
Order By: Relevance
“…Similarly, the distance between the embeddings of these face stimuli is larger when presented upright than inverted in the higher layers of a face-trained but not object-trained DCNN. A face inversion effect in a DCNN was also recently reported by Tian and colleagues 30 . Another evidence for the specificity of the face processing system of humans and DCNNs, to the stimuli it was trained with, is the other race effect.…”
Section: Discussionsupporting
confidence: 70%
“…Similarly, the distance between the embeddings of these face stimuli is larger when presented upright than inverted in the higher layers of a face-trained but not object-trained DCNN. A face inversion effect in a DCNN was also recently reported by Tian and colleagues 30 . Another evidence for the specificity of the face processing system of humans and DCNNs, to the stimuli it was trained with, is the other race effect.…”
Section: Discussionsupporting
confidence: 70%
“…Abudarham and colleagues (2021) showed that face-trained but not object-trained DCNNs are sensitive to the same view-invariant, critical facial features used by humans for face recognition. Recent studies have also shown that face-trained DCNNs generate a face inversion effect, similar to the well-established effect shown in humans 810 . Finally, face recognition DCNNs show better classification for the race of faces they are trained with 1113 , similar to the other-race effect, which has been extensively investigated in humans 14,15 .…”
Section: Introductionsupporting
confidence: 71%
“…A pure semantic DNN increases the total explained variance in human memory to 67%. Overall, these findings show that visualsemantic and semantic DNNs significantly improve the prediction of human representations of familiar faces, beyond the pure visual algorithm that has been so far used to model human face representations 3,4,[6][7][8]10,11,[28][29][30] .…”
Section: As Shown Inmentioning
confidence: 85%
See 1 more Smart Citation
“…To address these limitations in human studies, in the current study, we used deep convolutional neural networks (DCNNs) as computational models of perceptual expertise. DCNNs are brain-inspired algorithms that reach humanlevel performance and generate human-like representations for objects and faces [31][32][33][34][35][36]. These models can be trained to classify images from different domains at different levels of categorization [23].…”
Section: Introductionmentioning
confidence: 99%